Analisis Kerusakan Jalan dan Penanganannya Pada Ruas Jalan Timor Raya Km. 4 – Km. 7 - Kumalawati, Andi; Radja Pono, Hilary Melanthya; Bunganaen, Wilhelmus (JURNAL FORUM TEKNIK SIPIL (J-ForTekS), 2023)
The existence of highways is very necessary to support the pace of economic growth, agriculture, and other sectors. Given the important benefits, it is for this reason that the road construction and maintenance sector is a priority to be researched and developed in implementation planning, as well as maintenance. The purpose of this study was to determine the value of the Pavement Condition Index (PCI), identify the factors causing damage to Jalan Raya Timor Km.4-Km.7 and find out the type of repair according to the type and level of damage to Jalan Raya Timor Km.4 - Km.7. The average PCI value for Jalan Timor Raya Km.4 - Km.7 was 59.67 and there were 6 types of damage that occurred on Jalan Timor Raya Km.4 - Km.7, Oesapa Village, Kupang City, namely grain release, holes, crocodile skin cracks, bleeding, corrugation and collapse. The percentage of damage that occurs according to the type of damage is Grain Release 17.29%, Collapse 40.61%, Bleeding 31.72%, Crocodile Skin Cracks 2.44%, Holes. Factors causing damage to Jalan Timor Raya Km.4 – Km.7 include: Excessive vehicle loads so that the strength of the bottom structure of the road pavement or the road pavement structure itself is not able to carry it, poor compaction implementation, uneven or excessive use of asphalt and traffic that clears before the pavement is firmly used.